2019
DOI: 10.15640/jsbed.v7n1a5
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Culture and Orientations of SME Owners/Managers in the Kingdom of Bahrain

Abstract: Purpose: This paper seeks to examine the mediating influence of entrepreneurial culture and orientations on the development of the entrepreneurial performance, spirit and endeavors of Small and Medium Enterprises owners/managers in the Kingdom of Bahrain. The paper also determines some of the problems besetting the SME owners/managers along their cultural values and entrepreneurial orientations. Design/Methodology/Approach: This paper is a qualitative study and will use a descriptive correlation research desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Studies revealed that SME activity is affected by financial issues, the most pressing of which is the fear of taking out a loan (Hampel-Milagrosa et al , 2015) and a lack of available financing (Bunagan and Sison, 2019). Kebaili et al (2015) have identified seven factors as the main barriers to start-ups in Qatar, namely, unavailability of funds, risk avoidance, fear of failure, market barriers, knowledge barriers, stress avoidance and attitudes towards change.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies revealed that SME activity is affected by financial issues, the most pressing of which is the fear of taking out a loan (Hampel-Milagrosa et al , 2015) and a lack of available financing (Bunagan and Sison, 2019). Kebaili et al (2015) have identified seven factors as the main barriers to start-ups in Qatar, namely, unavailability of funds, risk avoidance, fear of failure, market barriers, knowledge barriers, stress avoidance and attitudes towards change.…”
Section: Resultsmentioning
confidence: 99%
“…Many articles recognise the negative effects of a lack of competencies on SME activity. Some of the following barriers are mentioned: difficulty establishing administration frameworks (Arshi and Burns, 2018; Abdullah and Mansor, 2018), a lack of infrastructure and regulatory frameworks (Bjørn and Boulus-Rødje, 2018; Bunagan and Sison, 2019), a lack of cooperation between individuals, organisations and sectors within the entrepreneurial environment (Bawaneh and Al-Abbadi, 2017) and a lack of legal advisors for entrepreneurs (Abu-Jalil, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Sekhar et al, 2018;Way et al, 2018;Ubeda-Garc ıa et al, 2017), however, to what length it can be instrumental for SMEs is yet to be unveiled. Harney and AlKhalaf (2021), in their review of 25 years of studies Bunagan and Sison, 2019;Joshi and Ramadhan, 2002;Khan and Khan, 1992), and an absolute absence of scholarly evidence on flexible HRM, empowering leadership, and firm performance associations. Henceforth, the present study responds to substantial gaps in the body of knowledge on the aforementioned factors and helps interested readers guide and educate about SME performance.…”
Section: Smes In Contextmentioning
confidence: 99%
“…Moreover, in connection to Bahrain, extant literature outlines very limited credible research studies on SMEs (e.g. Bunagan and Sison, 2019; Joshi and Ramadhan, 2002; Khan and Khan, 1992), and an absolute absence of scholarly evidence on flexible HRM, empowering leadership, and firm performance associations. Henceforth, the present study responds to substantial gaps in the body of knowledge on the aforementioned factors and helps interested readers guide and educate about SME performance.…”
Section: Smes In Contextmentioning
confidence: 99%
“…Developing sustainable MSEs is a great challenge among nations and regions. For example, a study in Bahrain suggested that the government should build up 'entrepreneurial spirits' among citizens to foster new firm establishment [4]. In this endeavor, the university's role in helping MSEs through education and training is relevant [5].…”
Section: Introductionmentioning
confidence: 99%